2023
DOI: 10.1200/go.22.00232
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of the International Cancer Control Partnership: Promoting National Cancer Control Plans to Shape the Health System Response for Cancer Control

Abstract: Growing premature mortality because of cancer is an increasing public health concern in all countries. This article reviews 10 years of the International Cancer Control Partnership (ICCP) considering the themes of National Cancer Control Plan (NCCP) support, technical assistance, governance, and the renewed momentum of global calls to action. ICCP has provided key resources for the cancer community by hosting a portal with national cancer control and noncommunicable disease (NCD) plans, strategies, guidelines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…There is a broad and growing recognition that inclusion in high‐level plans aids the implementation of higher quality cancer care by strengthening governance, aligning strategic direction and prioritising resource allocation 14,15,35 . NCCPs aligned with National Health Plans can have impact in moving implementation forward.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a broad and growing recognition that inclusion in high‐level plans aids the implementation of higher quality cancer care by strengthening governance, aligning strategic direction and prioritising resource allocation 14,15,35 . NCCPs aligned with National Health Plans can have impact in moving implementation forward.…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad and growing recognition that inclusion in high-level plans aids the implementation of higher quality cancer care by strengthening governance, aligning strategic direction and prioritising resource allocation. 14,15,35 NCCPs aligned with National Health Plans can have impact in moving implementation forward. This review found a majority of plans do not contain significant reference to psycho-oncology across the cancer continuum; fewer focusing on post-treatment and few having clear objectives despite guidance available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations